An Investigation into Speaker and Headphone-Based Immersive Audio for VR and Digital Gaming Applications - Marais, Kyle Donald (Rhodes University, Faculty of Science, Department of Computer Science)
There is a need for audio spatialization in gaming and Virtual Reality applications. If the sounds of a virtual environment correspond to their visual sources, the user will feel more engrossed or immersed in the environment and will more likely suspend their disbelief. Certain software, such as Audio Middleware, works in cooperation with game engine software to facilitate the audio requirements for virtual environment and game developers. This thesis provides a comparison of speaker and headphone-based immersive audio systems in the context of Virtual Reality, with the aim of determining and analyzing the differences between both systems. Accordingly, the thesis describes the implementation of an enhanced speaker-based Audio Middleware sound capability for Unity game engine developers. The capability leverages the functionality of a popular Audio Middleware software suite, FMOD, and a speaker-based spatialization system, ImmerGo. The headphone spatialization system that was contrasted with the bespoke speaker-based system was the Oculus Audio Spatializer. A sample VR application that employs both spatialization systems was developed, and served as the testing framework for the experimentation. Ultimately, the application provides users with 3D sound control in real time. Thus, via the use of the Leap Motion controller and Oculus Rift Development Kit 2 Head-Mounted Display (HMD), users can select an audio source with a gesture, and then subsequently pan the audio around them in three-dimensional space. The findings of the research suggest that the speaker-based system facilitated greater immersion than the headphone-based system, despite the headphone-based system providing more accurate audio localization and a higher 'perceived audio quality'.
Keywords: Virtual reality; Sound and music computing; Motion capture; Software engineering; Applied computing; Computer graphics